ß-Glucuronidase as a new potent biomarker in the diagnosis and prognosis of organophosphorus toxicity - Kale, Bhagwat (International Journal of Biological Research, 2013)
Background: Organophosphorus poisoning occurs as a result of accidental exposure, suicidal and homicidal attempts. Organophosphorus compounds are known to cause selective release of liver microsomal ß-glucuronidase (BG) into serum. Dissociation of the egasyn – ß-glucuronidase complex in the liver by organophosphorus compounds was followed by a massive release of ß-glucuronidase from liver into the serum. Objectives: There are few papers suggesting increase in activity of ß-glucuronidase (BG) in serum of experimental animals subjected to organophosphorus poisoning. But, still there is less or no such study in human beings having organophosphorus poisoning. Thus, aim of our this research was to estimate and correlate activity of ß-glucuronidase (BG) in different stages of organophosphorus poisoning. Methods: ß-glucuronidase (BG) activity was determined by Goldstein method. Results and Conclusions: We found that the serum activity of ? – glucuronidase (BG) proportionally increases (p < 0.01) and correlates with severity of organophosphorus poisoning. Further, there was found a significant increase in ? – glucuronidase (BG) activity in low dose (mild) poisoning also. Thus, ? – glucuronidase (BG) can be used as a potent biochemical marker in the diagnosis and prognosis of organophosphorus poisoning along with acetylcholinesterase or may also without acetylcholinesterase.